Slowly, Slowly, Slowly, Said the Sloth - Carle, Eric; Goodall, Jane (London Puffin books, 2005)
A Very Hungry Caterpillar colouring book which is a black and white version of the original book. Eric Carle fans and budding illustrators can now bring this bestselling story to life, in their own colours, and at the same time enjoy reading their favourite story
Hobbies
2
Keywords: Hobbies